Sugammadex and anaphylaxis: An analysis of 33 published cases - Baris Arslan; Tuna Sahin; Hatice Ozdogan (Wolters Kluwer Medknow Publications, 2021)
In this study, the published sugammadex-induced anaphylaxis reports were reviewed to determine similarities in their presentation during anesthesia. PubMed was searched for sugammadex-induced anaphylaxis without time limitation. Reports were evaluated if they were in English and met the criteria of anaphylaxis determined by the World Allergy Organization. Two independent reviewers extracted and assessed the data using predesigned data collection forms. In total, 23 suitable articles were found and 33 sugammadex-induced anaphylaxis cases were included in the study. The mean age was 43.09 years (from 3-89 years) and 17 (51.5%) of the patients were female. Considering all reported cases, the average onset time of anaphylaxis was 3.08 min, with a median of 3 min (range 1-8 min). The most common signs and symptoms were hypotension, tachycardia, erythema, and desaturation. Of the 20 patients who underwent confirmatory skin testing, 15 had a positive skin reaction for sugammadex. Epinephrine was not given when indicated in about 25% of cases. Sugammadex-induced anaphylaxis onset time was less than 5 min in 92.3% of all the reported cases. Rapid diagnosis and early recognition of signs and symptoms of anaphylaxis are essential for a favorable prognosis. Treatment needs to be started as soon as possible to ensure the best outcome for the patient.